Sport, physical activity and criminal justice : politics, policy and practice - Morgan, Haydn; Parker, Andrew, 1965- (New York, NY : Routledge, 2023)
"This book explores the various ways in which participation in sport and physical activity might contribute to effective solutions within criminal justice systems. With shifting debates around criminal justice and the need for policy and practical solutions to extend beyond tougher and longer sentencing, this book is important reading for students, researchers and practitioners working in sports pedagogy, sport-for-development, sport and leisure management, sports coaching, physical education, criminology, youth work, youth studies, social work and health studies"--
OCLC-licensed vendor bibliographic record.
Keywords: Prisoners -- Recreation; Criminals -- Rehabilitation; Sports -- Sociological aspects; SPORTS & RECREATION / Sociology of Sports; SOCIAL SCIENCE / Criminology